"Racialized Terrorism" in the American South: Do Completed Lynchings Tell an Accurate Story?. Issue 4 (20th July 2018) - Tolnay, Stewart E.; Beck, E. M.
Abstract : Past empirical research into the history of racially motivated mob violence in the American South has relied almost exclusively on the record of completed lynchings. In this article, we propose that a better definition of "racialized terrorism" would also include the record of lynching threats. Using a newly available confirmed inventory of lynching threats for 11 Southern states from 1880 to 1929, we demonstrate that the total quantum of racialized terrorism nearly doubles when completed lynchings and lynching threats are combined, with some states and decades affected more than others. Parallel analyses suggest that previous conclusions regarding important environmental predictors of Southern mob violence, such as agricultural specialty, political party strength, and racial population composition, are robust to an expansion of racialized terrorism to include threatened lynchings. However, sufficient differences are found between the predictors of completed and threatened lynchings to suggest the need for future researchers to consider broadening the measurement of racialized terrorism.